Whole-Inactivated Influenza Virus Is a Potent Adjuvant for Influenza Peptides Containing CD8+ T Cell Epitopes - Soema, Peter C.; Rosendahl Huber, Sietske K.; Willems, Geert-Jan; Jacobi, Ronald; Hendriks, Marion; Soethout, Ernst; Jiskoot, Wim; de Jonge, Jørgen; van Beek, Josine; Kersten, Gideon F. A.; Amorij, Jean-Pierre (Frontiers in Immunology, 2018)
Influenza peptide antigens coding for conserved T cell epitopes have the capacity to induce cross-protective influenza-specific immunity. Short peptide antigens used as a vaccine, however, often show poor immunogenicity. In this study, we demonstrate that whole inactivated influenza virus (WIV) acts as an adjuvant for influenza peptide antigens, as shown by the induction of peptide specific CD8+ T cells in HLA-A2.1 transgenic mice upon vaccination with the influenza-M1 derived GILGFVFTL peptide (GIL), formulated with WIV. By screening various concentrations of GIL and WIV, we found that both components contributed to the GIL-specific T cell response. Whereas co-localization of the peptide antigen and WIV adjuvant was found to be important, neither physical association between peptide and WIV nor fusogenic activity of WIV were relevant for the adjuvant effect of WIV. We furthermore show that WIV may adjuvate T cell responses to a variety of peptides, using pools of either conserved wild-type influenza peptides or chemically altered peptide ligands. This study shows the potential of WIV as an adjuvant for influenza peptides. The simple formulation process and the solid safety record of WIV make this an attractive adjuvant for T cell peptides, and may also be used for non-influenza antigens.